The German Werkbund : The Politics of Reform in the Applied Arts - Campbell, Joan, 1929- (Book collections on Project MUSE., 1978)
For years one of Germany's foremost cultural organizations, the Werkbund included in its membership such pioneers of the modern movement as Henry van de Velde, Hermann Muthesius, Walter Gropius, and Mies van der Rohe. Joan Campbell traces its history from its founding in 1907 to 1934, when it was absorbed into the bureaucracy of the National Socialist State.The Werkbund set out to prove that organized effort could revitalize the applied arts and architecture. In addition to acting as an agent of reform, it provided a forum for the debate of such broad concerns as the need to restore joy and dignity to work in modem industry.Originally published in 1978.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.